Penerapan Game Educaplay “Froggy Jumps” sebagai Media Interaktif Pembelajaran Bahasa Arab di MA Darul Faizin - M.Waviyul Ahdi; Irma Rahimah; Khoirun Niswah; Muhammad Abror Rosyidin (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2026)
The game-based learning media Educaplay Froggy Jumps is intended to increase the interactivity of Madrasah Aliyah (MA) students when learning Arabic. Students can be motivated to learn Arabic through this game, which combines entertainment and educational elements. Needs analysis, media design, implementation, and evaluation of the effectiveness of learning media are all part of this research methodology. The research results show that interactive game media such as Educaplay Froggy Jumps significantly increase student participation and interaction when learning Arabic. Students are also more enthusiastic and active in understanding Arabic vocabulary and sentence structures. In conclusion, this research shows that interactive game media such as Educaplay Froggy Jumps can be an effective tool for learning foreign languages ​​at the elementary level. Keywords:Learning Media, Educaplay Games, Arabic Learning, Madrasah Aliyah